Rancang Bangun Media Pembelajaran Mengenal Adat dan Budaya Indonesia Berbasis Multimedia Interaktif (Current Research in Education: Conference Series Journal, 2023)
The increasing number of foreign cultures entering Indonesia increasingly threatens Indonesian culture to disappear or be claimed by other countries. Seeing so many incidents, it is necessary to introduce customs and culture in Indonesia, especially elementary school students (SD) with the aim of growing a sense of love for Indonesian culture. So the researchers designed an interactive multimedia-based learning media. The methods used to collect data are interviews and literature studies. The research method carried out refers to research and development (Research and Development/ RnD). This final project will introduce 34 provinces in Indonesia with material content in the form of traditional clothes, traditional houses, languages, folk songs and special foods from each province in Indonesia. The material becomes more interesting by inserting interactive animations where the user can easily control the tools they operate. And it is also hoped that this interactive multimedia can increase the learning motivation of elementary school students related to culture in Indonesia and eliminate boredom with monotonous learning activities.